EFEKTIVITAS RELAKSASI OTOT PROGRESIF TERHADAP STRES MAHASISWA YANG SEDANG MENYUSUN TUGAS AKHIR INSTITUT KESEHATAN MITRA BUNDA - Huzaima, Huzaima; Heroyanto, Heroyanto; Ridmadhanti, Suci (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
An absolute requirement for completing an educational program, thesis is frequently regarded as a threat or a challenge. At this stage, students must complete the thesis in accordance with a predetermined time and other academic load. This sometimes causes distress physiologically, psychologically, and behaviorally or often called stress. Results of a preliminary study indicated that most of students experienced symptoms referring to stress during the process of completing the thesis. One of the non-pharmacological methods used to cope with stress is progressive muscle relaxation therapy.To identify the effects of progressive muscle relaxation on stress in students writing thesis at Mitra Bunda Health Institute. This research is a true experimental research with pretest posttest with control group method. Research subjects were all final semester students. Samples were taken using proportional random sampling. The experimental group consisted of 20 students and the control group consisted of 19 students. Data were Analyzed using Paired T test and Independent T Test.The stress level of students in the experimental group before the progression muscle relaxation therapy was in the category of moderate stress numbering 11 students (55%) and after the progression muscle relaxation therapy numbering 9 students (45%). Meanwhile, in the pretest the control group was most in the category of normal stress numbering 10 people (55%) and in the posttest 10 students (55%) remained in the normal category. The progression muscle relaxation therapy in the experimental group indicated sig of 0.004 (p <0.05) and in the control group indicated sig of 0.564 (p> 0.05). There is an effect of giving progressive muscle relaxation on stress in students writing thesis at Mitra Bunda Health Institute.